Les aptitudes technologiques des bactéries lactiques isolées à partir de produits laitiers artisanaux - Adjed, Aya; Benyehia, Khadidja Ikram (My University, 2023)
In this in-depth study, we undertook a comprehensive assessment of the technological capabilities of twelve distinct lactic bacterial strains, isolated from three artisanal dairy products, namely "ben, jben and zebda". These dairy products were made from raw cow’s milk, providing an authentic context for the study of lactic bacterial strains. The bacterial strains were identified by the MALDI-TOF MS technique, then revived and purified before testing their technological abilities. We focused on their proteolytic, lipolytic, texturing and flavouring properties, as these characteristics play an essential role in food production. The results obtained revealed a marked diversity in the technological capacities of the lactic bacterial strains studied. Of the twelve strains examined, only two, identified as strains 108 and 111, exhibited proteolytic activity, with inhibition zone diameters of 21mm and 19mm, respectively. Remarkably, strain 108 was also positive in terms of flavouring activity. However, none of the strains studied exhibited textural or lipolytic activity. These results underline the crucial importance of carefully selecting the appropriate strains according to the specific characteristics sought in the food industry, particularly with regard to the texture, flavour and aroma of the final products.
Keywords: Technological properies; revivification; lactic bacterial strains; flavor; aroma; proteolytic power